Legal recognition of same-sex partnership as a political claim: Just aporias, critical (im)possibilities. Issue 2 (1st October 2018) - Papanagiotou, Athina
Legal recognition constitutes one of the most topical questions for LGBTQI+ movements and the relative theory. Legal recognition of same-sex partners is construed, for a part of the movement, as a subversive, emancipatory political claim which seeks to ensure a safe legal ground, where the partners will enjoy visibility and rights comparable to those provided to opposite-sex married couples. However, the historicization of partnership recognition, and more specifically of the institution of marriage, reveals its links to ownership, reproduction of the nation, church, gender discrimination, exclusion as well as to the classification of erotic practices, intimacy and relationality. Addressing the Greek context, this article explores the aporetic tensions between the political demand of recognition and its radical potential, on the one hand, and the context (historical, political and social) of the institution of marriage on the other. Is there any justice in inclusion and how should we understand it? Are all the stories of recognition, hence of inclusion and subjection to law, the same? What does law sustain when its idiom expands, for instance in the case of the new Greek civil partnership agreement? Where is the place ‐ if any ‐ of justice and can it be inhabited by law? Is law something that we 'cannot not want', as Gayatri Chakravorty Spivak puts it? Finally, does the position from which these questions are posed matter? The article does not attempt to respond to the dilemmatic question 'for or against' legal recognition, but complicates it with analytical tools borrowed from critical theory, feminist and queer theory and Derridean deconstruction.